(untitled) (Communication & Society, 2020)
The aim of this paper is to contrast whether cognitive memory and emotional recall related to a tragic event and exposure to advertisements that evoke such an experience generates a negative emotional change in the target. We performed an experiment that analyzes emotional changes derived from advertisements featured in the national press ten years after terrorist attacks. We chose the attacks: September 11, 2001, in New York City, and March 11, 2004, in Madrid and analyze the cognitive recall in a set of Spanish and United States focus groups. The results show a significant emotional change in the respondents after the advertisement visualization that is more strongly linked to the recall of a negative event than to the advertisement creativity.